Etanercept 50 mg once weekly is as effective as 25 mg twice weekly in patients with ankylosing spondylitis. Issue 12 (12th September 2006) - van der Heijde, D; Da Silva, J C; Dougados, M; Geher, P; van der Horst-Bruinsma, I; Juanola, X; Olivieri, I; Raeman, F; Settas, L; Sieper, J; Szechinski, J; Walker, D; et al.
Abstract : Objective: To compare the efficacy, pharmacokinetics and safety of etanercept 50 mg once weekly with 25 mg twice weekly and placebo in patients with ankylosing spondylitis. Methods: A 12-week, double-blind, placebo-controlled study compared the effects of etanercept 50 mg once weekly, etanercept 25 mg twice weekly and placebo in 356 patients with active ankylosing spondylitis (3:3:1 randomisation, respectively). The primary end point was the proportion of patients achieving a response at week 12 based on the Assessment in Ankylosing Spondylitis Working Group criteria (ASAS 20). The pharmacokinetics of etanercept 50 mg once weekly and 25 mg twice weekly were analysed. Results: Baseline characteristics and disease activity were similar among the three groups: etanercept 50 mg once weekly, etanercept 25 mg twice weekly and placebo. The percentage of patients discontinuing therapy was 9.0%, 9.3% and 13.7% for the three respective groups. ASAS 20 response at 12 weeks was achieved by 74.2% of patients with etanercept 50 mg once weekly and 71.3% of those with etanercept 25 mg twice weekly, both significantly higher than the percentage of patients taking placebo (37.3%, p<0.001). Percentages of patients with ASAS 5/6 response (70.3%, 72.0% and 27.5%, respectively; p<0.001) and those with ASAS 40 response (58.1%, 53.3% and 21.6%, respectively; p<0.001) followed a similar pattern. Significant improvement (p<0.05) was seen in measures of disease activity, back pain, morning stiffness and C reactive protein levels as early as 2 weeks. Serum etanercept exposure was similar between the etanercept groups. Incidence of treatment-emergent adverse events, including infections, was similar among all three groups, and no unexpected safety issues were identified. Conclusions: Patients with ankylosing spondylitis can expect a comparable significant improvement in clinical outcomes with similar safety when treated with etanercept 50 mg once weekly or with 25 mg twice weekly.